Raman investigation of different polytypes in SiC thin films grown by solid-gas phase epitaxy on Si (111) and 6H-SiC substrates - PEROVA, TANIA (My University, 2010)
Raman spectroscopy was applied to investigate a series of SiC films grown on Si and 6HSiC substrates by a new method of solid gas phase epitaxy. During the growth characteristic voids are formed in Si at the SiC/Si interface. Raman peak position, intensity and linewidth were used to characterize the quality and the polytype structure of the SiC layers. A large enhancement in the peak intensity of the transverse optical and longitudinal optical phonon modes of SiC is observed for the Raman signal measured at the voids. In addition, scanning electron microscopy and atomic force microscopy were used to investigate the surface morphology of SiC layers.
PUBLISHED
Keywords: Raman spectroscopy; solid-gas phase epitaxy; voids; Raman enhancement; Nanoscience & Materials